HUBUNGAN SISTEM BAGI HASIL DI LEMBAGA KEUANGAN SYARIAH TERHADAP KEINGINAN NASABAH UNTUK BERINVESTASI Survei di Baitul Maal wat Tamwil (BMT) Safinah Klaten - Suyatmin Suyatmin; Atwal Arifin (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2008)
This study aims to analyze the profit sharing system of Syari’ah Financial Organization with the clients’ attitude in doing an investment and know whetheror there is an opportunity for developing it. Thestatistic analysis used the product momentwith the questionnaires for the clients of Baitul Maal wat Tamwil SAFINAH Klaten. The correlation of the profit sharing and doing-an-investment was significant. It could be concluded that the people’s confident level in the system applied to the organization was very significant. Thus, more and more clients from year to year, it is possible that there will be an opportunity for developing it.